Ultrasound-assisted extraction and solvent extraction of papaya seed oil: crystallization and thermal behavior, saturation degree, color and oxidative stability - Samaram, Shadi; Mirhosseini, Hamed; Tan, Chin Ping; Mohd Ghazali, Hasanah (Elsevier, 2014)
The main objective of the current work was to evaluate the suitability of ultrasound-assisted extraction (UAE) as compared to different conventional methods (i.e. Soxhlet extraction (SXE) and solvent extraction (SE)) for the recovery of papaya seed oil (PSO) from Malaysian Sekaki papaya variety. The efficiency of different extraction methods was evaluated by comparing the physicochemical properties and oxidative stability of the extracted PSOs. The main analytical tests were iodine value (IV), unsaponifiable matters, color, crystallization and melting behavior, peroxide value (PV), anisidine value (AV), and TOTOX value (TV). Results indicated that extraction method (UAE) considerably influenced the physicochemical properties of the extracted PSO. In this study, UAE provided PSO with significantly (p < 0.05) lighter color, lower unsaponifiable matters (1.35%) and higher oxidative stability (PV, 0.18 mequiv./kg; TV, 0.93) than conventional extraction techniques (SXE and SE techniques).